2015
DOI: 10.1128/jcm.00249-15
|View full text |Cite
|
Sign up to set email alerts
|

Global Multilocus Sequence Type Analysis of Chlamydia trachomatis Strains from 16 Countries

Abstract: eThe Uppsala University Chlamydia trachomatis multilocus sequence type (MLST) database (http://mlstdb.bmc.uu.se) is based on five target regions (non-housekeeping genes) and the ompA gene. Each target has various numbers of alleles-hctB, 89; CT058, 51; CT144, 30; CT172, 38; and pbpB, 35-derived from 13 studies. Our aims were to perform an overall analysis of all C. trachomatis MLST sequence types (STs) in the database, examine STs with global spread, and evaluate the phylogenetic capability by using the five t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 44 publications
(86 reference statements)
7
44
1
Order By: Relevance
“…Two molecular typing schemes exist, using either multiple locus variable number tandem repeat analysis (MLVA), which has only identified seven MLVA sequence types (MTs) [19, 20], or multiple locus sequence typing (MLST) [19, 21], where only six MLST sequence types (STs) have been defined. This is in sharp contrast to greater diversity in other species of Chlamydia [2123]. Studies on limited numbers of samples suggest that C. abortus isolates in livestock appear to be largely monomorphic: low diversity is observed throughout the genome, even within the plasticity zone (PZ), a region of high genomic variation in other chlamydial species [6, 9, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Two molecular typing schemes exist, using either multiple locus variable number tandem repeat analysis (MLVA), which has only identified seven MLVA sequence types (MTs) [19, 20], or multiple locus sequence typing (MLST) [19, 21], where only six MLST sequence types (STs) have been defined. This is in sharp contrast to greater diversity in other species of Chlamydia [2123]. Studies on limited numbers of samples suggest that C. abortus isolates in livestock appear to be largely monomorphic: low diversity is observed throughout the genome, even within the plasticity zone (PZ), a region of high genomic variation in other chlamydial species [6, 9, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genome sequencing data reveals that omp A must not be relied on solely as a marker for genotyping, as recombination of all or parts of this gene within and between biovars is evident 15. There are now several very highly discriminating multilocus molecular typing systems, including multi locus sequence typing (MLST), for C. trachomatis that allow differentiation and subgrouping of isolates within a genotype 13 16 17 . W4–6 The multilocus variable number tandem repeat (VNTR) analysis plus analysis of the omp A gene (MLVA- omp A) high-resolution genotyping system of Pedersen et al ,13 has been successfully evaluated,18 and recent work has shown that the VNTR marker sequences are stable and therefore ideal for genotyping 19.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have acquired a more complete view of the complex epidemiology of C. trachomatis [18,19]. In this study, we describe for the first time an onsite ecological displacement of a previous variant, and this replacement could also help to spread the infection more easily.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, several authors defined clusters of transmission, identifying nodes with only G genotypes in MSM [22]. Furthermore, these publications consistently reported clusters with G and J genotypes in the MSM population, and they also found genotype J in the heterosexual population [19,23]. These results suggest that genotype J could be a 'bridge genotype'.…”
Section: Discussionmentioning
confidence: 91%